Tmax Mismatch Ratio to Identify Intracranial Atherosclerotic Stenosis‐Related Large‐Vessel Occlusion Before Endovascular Therapy - Takeshi Yoshimoto; Manabu Inoue; Kanta Tanaka; Junpei Koge; Masayuki Shiozawa; Naruhiko Kamogawa; Hiroyuki Ishiyama; Soichiro Abe; Hirotoshi Imamura; Hiroharu Kataoka; Masatoshi Koga; Masafumi Ihara; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background We aimed to clarify which time‐to‐maximum of the tissue residue function (Tmax) mismatch ratio is useful in predicting anterior intracranial atherosclerotic stenosis (ICAS)–related large‐vessel occlusion (LVO) before endovascular therapy. Methods and Results Patients with ischemic stroke who underwent perfusion‐weighted imaging before endovascular therapy for anterior intracranial LVO were divided into those with ICAS‐related LVO and those with embolic LVO. Tmax ratios of >10 s/>8 s, >10 s/>6 s, >10 s/>4 s, >8 s/>6 s, >8 s/>4 s, and >6 s/>4 s were considered Tmax mismatch ratios. Binominal logistic regression was used to identify ICAS‐related LVO, and the adjusted odds ratio (aOR) and 95% CI for each Tmax mismatch ratio increase of 0.1 were calculated. A similar analysis was performed for ICAS‐related LVO with and without embolic sources, using embolic LVO as the reference. Of 213 patients (90 women [42.0%]; median age, 79 years), 39 (18.3%) had ICAS‐related LVO. The aOR (95% CI) per 0.1 increase in Tmax mismatch ratio in ICAS‐related LVO with embolic LVO as reference was lowest with Tmax mismatch ratio >10 s/>6 s (0.56 [0.43–0.73]). Multinomial logistic regression analysis also showed the lowest aOR (95% CI) per 0.1 increase in Tmax mismatch ratio with Tmax >10 s/>6 s (ICAS‐related LVO without embolic source: 0.60 [0.42–0.85]; ICAS‐related LVO with embolic source: 0.55 [0.38–0.79]). Conclusions A Tmax mismatch ratio of >10 s/>6 s was the optimal predictor of ICAS‐related LVO compared with other Tmax profiles, with or without an embolic source before endovascular therapy. Registration clinicaltrials.gov. Identifier NCT02251665.